Three new species of herb gall wasps (Hymenoptera: Cynipidae) from Turkey - Azmaz, Musa; Katılmış, Yusuf (European Journal of Taxonomy, 2021)
Three new species of herb gall wasps (Cynipidae: Aulacideini and Phanacidini) are described from Turkey. Aulacidea turguti sp. nov. induces galls on Hieracium patentissimum Freyn & Sint. ex Freyn, 1895 (Asteraceae) and was collected in Gümüşhane province, Phanacis ciceki sp. nov. and Phanacis urhani sp. nov. were collected in Gümüşhane and Ordu Provinces, the former inducing galls on Picris sp. and the latter on Cirsium vulgare (Savi) Ten., 1835–36 (Asteraceae). SEM images, gall photos, distribution, biology, and diagnostic morphological characteristics of the three new species are provided.